Elements of Structural Syntax - Tesnière, Lucien (John Benjamins Publishing Company, 2015)
This volume is now finally available in English, sixty years after the death of its author, Lucien Tesnière. It has been translated from the French original into German, Spanish, Italian, and Russian, and now at long last into English as well. The volume contains a comprehensive approach to the syntax of natural languages, an approach that is foundational for an entire stream in the modern study of syntax and grammar. This stream is known today as dependency grammar (DG). Drawing examples from dozens of languages, many of which he was proficient in, Tesnière presents insightful analyses of numerous phenomena of syntax. Among the highlights are the concepts of valency and head-initial vs. head-final languages. These concepts are now taken for granted by most modern theories of syntax, even by phrase structure grammars, which represent, in a sense, the opposite sort of approach to syntax from what Tesnière was advocating.